2003
DOI: 10.2466/pr0.2003.92.1.275
|View full text |Cite
|
Sign up to set email alerts
|

Greek Students' Attitudes toward Physical Activity and Health-Related Behavior

Abstract: A three-wave study over one year with 882 adolescents, aged 10 to 16 years at the initial testing, examined psychosocial variables regarding four health-related behaviors: exercise, eating fruit, smoking, and drug use. Analysis showed that during the stages of the study, high school students' exercise behavior decreased and their smoking behavior increased as well as their willingness to use drugs. It seems that study of physical education and health education during adolescence must take into account the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Despite calls for interventions that address multiple health behaviors concurrently [12] [25] [26] most of the preventive programs for adolescents target solely smoking behavior or smoking related variables. Addressing two health-related behaviors concurrently, Hassandra, Theodorakis, Kosmidou, Grammatikopoulos, and Hatzigeorgiadis [27], applied a smoking prevention program, named "I do not smoke, I exercise", to 210 students of junior high school.…”
Section: Exercise For Smoking Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite calls for interventions that address multiple health behaviors concurrently [12] [25] [26] most of the preventive programs for adolescents target solely smoking behavior or smoking related variables. Addressing two health-related behaviors concurrently, Hassandra, Theodorakis, Kosmidou, Grammatikopoulos, and Hatzigeorgiadis [27], applied a smoking prevention program, named "I do not smoke, I exercise", to 210 students of junior high school.…”
Section: Exercise For Smoking Preventionmentioning
confidence: 99%
“…Large scale surveys showed that there is a link between tobacco use and other unhealthy behaviors, and that people generally adopt an overall healthy or unhealthy lifestyle [26] [30] [31]. Theodorakis et al [32] examined the healthy and unhealthy behavioral profiles of Greek high school students.…”
Section: Exercise For Smoking Preventionmentioning
confidence: 99%
“…The program “I do not smoke, I exercise” is an effort for filling this gap in Greek schools involving a smoking prevention intervention and promoting exercise as an alternative healthy behavior. This dual emphasis of the program is important in the face of evidence suggesting decreased exercise behavior and increased smoking behavior among high school students (Theodorakis, Natsis, Papaioannou, & Goudas, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use has been well documented as the single most prevalent cause of premature death and disability [4]. At the same time, high school students decrease their exercise behaviour and increase their smoking behaviour [5], and adolescents expressing a firm commitment to physical fitness are less likely to be smokers [6,7].…”
Section: Introductionmentioning
confidence: 99%